The Effect of Credit Financing on Profitability PT Adira Dinamika Multi Finance Tbk with Receivables Turnover Ratio Analysis - Farman, Fanji; Maharani, Asyifa Ayu; Marlina, Dina (Journal of Business, Accounting and Finance, 2024)
This study analyzes the receivable turnover ratio (RTO) and the average time spent to collect receivables (Average Collection Period - ACP) at PT Adira Dinamika Multi Finance Tbk (ADMF) during the period 2014 to 2018. The research method used is "Library Research," which utilizes theories from books relevant to the topic of this study. The findings show that RTO increased in 2015, but decreased significantly in the following years, while ACP showed good efficiency in 2014 and 2015, but increased in the following years, indicating a decrease in efficiency in collection. Nevertheless, PT Adira still maintains a healthy collection period. This study highlights the importance of effective credit sales in influencing the profitability of the company, where higher receivables can increase profits. It is recommended that the company improve its receivables management by setting credit standards and conducting routine collections.